Effects of environmental instabilities on endpoint stiffness during the maintenance of human arm posture - Krutky, Matthew A. (2009)
Using the upper limb to manipulate objects or tools requires maintenance of stable arm posture. The ability to maintain stable postures is dependent on the mechanical properties of the arm, which can be characterized by estimates of endpoint stiffness. In this study we quantified the endpoint stiffness of the human arm during postural interactions with mechanically imposed unstable loads. The purpose was to determine the extent to which arm stiffness is adapted according to the mechanical properties of the environment during postural tasks. We estimated the endpoint stiffness of the right arms of eight subjects as they interacted with four haptic environments: rigid, unstable along the direction of maximal endpoint stiffness and orthogonal to this direction, and a high-strength unstable environment also aligned to the orientation of maximal endpoint stiffness. The size and orientation of endpoint stiffness were quantified for each haptic condition. Stiffness size was increased along the directions of the destabilizing environments (p<0.003). However, the environments had no significant effect on stiffness orientation (p>0.26). These findings suggest that at a fixed posture interactions with unstable environments can induce moderate, task-appropriate changes in limb mechanics that are tuned to the environment. However, these changes are small relative to those that can be obtained by changing limb posture.